2022
DOI: 10.1002/ffj.3701
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of aroma components and antioxidant activity of essential oil from Ocimum tenuiflorum leaves

Abstract: Ocimum tenuiflorum has a characteristic spicy, sweet and green aroma and has been used as a medicinal herb for various diseases in Ayurveda systems. This study aimed to investigate the aroma‐impact components and antioxidant activity of the essential oil from O. tenuiflorum leaves, grown in Sri Lanka, which was obtained by hydrodistillation. The volatile compounds in the essential oil were measured by gas chromatograph–mass spectrometry. The major components were caryophyllene oxide (23.8%), β‐caryophyllene (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Syn Kok Yeo et al [ 16 ] showed theβ-bisabolene isomer to be the main component of essential oil obtained from the medicinally valuable opoponax (Commiphora guidottii), and also suggested that β-bisabolene could be further studied for its application in the treatment of breast cancer. In the meantime, the major aroma constituent of -copaene, which has been identified in the fruits of Rubus ulmifolius [ 17 ], Criollo cacao [ 18 ], and Ocimum tenuiflorum leaves [ 19 ], is a complex, highly volatile, and extensively distributed plant compound [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Syn Kok Yeo et al [ 16 ] showed theβ-bisabolene isomer to be the main component of essential oil obtained from the medicinally valuable opoponax (Commiphora guidottii), and also suggested that β-bisabolene could be further studied for its application in the treatment of breast cancer. In the meantime, the major aroma constituent of -copaene, which has been identified in the fruits of Rubus ulmifolius [ 17 ], Criollo cacao [ 18 ], and Ocimum tenuiflorum leaves [ 19 ], is a complex, highly volatile, and extensively distributed plant compound [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…D-Limonene, a monocyclic terpene, offered a citrus aroma and was a major by-product of the citrus industry, commonly used as a flavor additive in foods, beverages, and fragrances 20) . α-copaene provided a woody aroma and was a major volatile compound in basil leaf essential oil 21) . 1,1,3-trimethyl-cyclohexane imparted a green and grassy aroma.…”
Section: Comparison Of Aroma-active Compounds In Sp Andmentioning
confidence: 99%
“…Three trained panellists (one male and two females, aged [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] were…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The aroma-active compounds in the three samples were analysed by the AEDA method. 28 The essential oils were stepwise diluted at 1:2, 1:4, 1:8, 1:16, …, 1:1024 ratios until any odour could be sniffed, and then AEDA analysis was halted. The flavour dilution (FD) factor was the maximum dilution at which the aroma compound could be detected…”
Section: Aroma Extract Dilution Analysis (Aeda)mentioning
confidence: 99%